Phenotypic evaluation of seedling and adult-plant stripe, leaf, and stem rust resistance in the A-genome diploid relatives of wheat - Sahin, Buket (Kansas State University, 2021)
Wheat (Triticum aestivum L.) is one of the most significant cereal crops in the world, ranking third following rice and maize. The various rust diseases that attack this crop – leaf rust (Puccinia triticina), stripe rust (Puccinia striiformis f. sp. tritici) and stem rust (Puccinia graminis f. sp. tritici) are important limitations for increasing wheat production in the world. In order to stay ahead of constantly evolving rust pathogens, it is necessary to increase genetic diversity by identifying genetic resistance from sources besides common wheat. Wild relatives of wheat are tractable sources of wheat rust resistance genes. The mini core collection of diploid A-genome species covering about 90 percent of the genetic variation of these species, including 59 accessions of T. monococcum subsp. aegilopoides, 24 accessions of T. monococcum subsp. monococcum, and 25 accessions of T. urartu, spanning their whole area of geographic distribution has been established by using genotype-by-sequencing (GBS). These accessions were evaluated for their seedling resistance to leaf rust, stripe rust, and stem rust under greenhouse conditions and were screened for adult plant resistance under both greenhouse and field conditions. Among the evaluated accessions in this study, T. monococcum subsp. monococcum showed a higher number of resistant accessions, followed by T. monococcum subsp. aegilopoides and T. urartu. Consequently, these species may have a high potential as donors of resistance to stripe rust, leaf rust, and stem rust.
Keywords: Stripe rust; Leaf rust; Stem rust; A-genome diploid relatives of wheat